2021
DOI: 10.1161/circulationaha.120.051898
|View full text |Cite
|
Sign up to set email alerts
|

Finerenone and Cardiovascular Outcomes in Patients With Chronic Kidney Disease and Type 2 Diabetes

Abstract: Background: The FIDELIO-DKD trial evaluated the effect of the nonsteroidal, selective mineralocorticoid receptor antagonist finerenone on kidney and cardiovascular (CV) outcomes in patients with chronic kidney disease (CKD) and type 2 diabetes (T2D) with optimized renin-angiotensin system blockade. Compared with placebo, finerenone reduced the composite kidney and CV outcomes. We report the effect of finerenone on individual CV outcomes and in patients with and without history of atherosclerotic CV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
187
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 212 publications
(197 citation statements)
references
References 39 publications
3
187
0
7
Order By: Relevance
“…Another drug of interest is finerenone (non-steroidal antagonist of the mineralocorticoid receptor). In the FIDELIO-DKD study, it shows a decrease in the incidence of cardiovascular events (HR, 0.86; 95% CI, 0.75 to 0.99; p = 0.034), as well as a decreased in kidney events (HR, 0.82; 95% CI, 0.73 to 0.93; p = 0.001) in patients with GFR 25-75 mL/min/1.73 m 2 [53,54].…”
Section: Hypertensionmentioning
confidence: 95%
“…Another drug of interest is finerenone (non-steroidal antagonist of the mineralocorticoid receptor). In the FIDELIO-DKD study, it shows a decrease in the incidence of cardiovascular events (HR, 0.86; 95% CI, 0.75 to 0.99; p = 0.034), as well as a decreased in kidney events (HR, 0.82; 95% CI, 0.73 to 0.93; p = 0.001) in patients with GFR 25-75 mL/min/1.73 m 2 [53,54].…”
Section: Hypertensionmentioning
confidence: 95%
“…Hyperkalemia was more common in the finerenone group, but discontinuation of the trial due to it was uncommon (2.3%). An additional subgroup analysis of these data showed that finerenone lowered the incidence of the composite cardiovascular outcome independent of preexisting cardiovascular diseases [133]. Another big phase 3 clinical trial was FIGARO-DKD (FInerenone in reducinG cArdiovascular moRtality and mOrbidity in Diabetic Kidney Disease), that investigated the role of finerenone in reducing major cardiovascular events, with slowing DKD progression as a prespecified secondary endpoint [15,134].…”
Section: Finerenone and Dkdmentioning
confidence: 99%
“…However, when looking at subgroups, some benefits of MR antagonists were found depending on the geographical origin of the patients, sex and age (Pitt et al, 2014;Pfeffer et al, 2015;Merrill et al, 2019). Recently published results show that new MR antagonists reduce the risk of chronic kidney disease progression and cardiovascular events in patients with chronic kidney disease and type 2 diabetes regardless of pre-existing cardiovascular problems (Bakris et al, 2020;Filippatos et al, 2021). Therefore, results from clinical trials suggest that an overactive RAAS is accountable for some of the cardiovascular changes occurring in cardiovascular diseases and in an attenuated form also during healthy aging.…”
Section: Cardiovascular Effects Of Mineralocorticoid Receptor and Agingmentioning
confidence: 99%